Regulatory disorders in infants: Assessment, Diagnosis, and Treatment - Cierpka, Manfred (SpringerLink Bücher, 2016)
This innovative book discusses current findings on regulatory disorders in infants and offers practical guidelines for diagnosis and intervention. Focusing on core infant and toddler concerns including crying, sleeping, feeding, clinginess, and aggression, it presents a developmental continuum from normal to disturbed behavior regulation and examines science-based strategies for halting this trajectory. Case examples and widely used tools illustrate diverse approaches to assessment and diagnosis, emphasizing nuances of parent-infant interactions and parents’ reactions that may fail to answer, or may even exacerbate, the child’s distress. And chapters outline counseling and therapy options for infants and parents, so that persistent problems do not become entrenched in children’s future behavior or lead to long-term family dysfunction. Among the topics covered: • Approaches to diagnosing regulatory disorders in infants. • Feeding disorders in infants and young children. • Developmentally appropriate vs. persistent defiant and aggressive behavior. • Treatment approaches for regulatory disorders. • Video and video feedback in counseling and therapy. Regulatory Disorders in Infants is an essential resource for clinicians and practitioners as well as researchers and graduate students in clinical child and school psychology, pediatrics, social work, psychiatry, and family studies